THE EXTENSION OF SUBJECTIVITY IN THE ARGENTINE CIVIL AND COMMERCIAL CODE (Perspectivas de las Ciencias Económicas y Jurídicas, 2020)
This paper proposes to analyze the impact of the sanction of the Civil and Commercial Code on the extension of the notion of person, by including in its articles the subjectivity of women, children, adolescents, non-heterosexual persons and persons with restricted capacity, all recognized by international law as persons in a situation of vulnerability. The research seeks to draw the difference between the current code and the Civil Code of Vélez Sarsfield in whose provisions the notion of person was identified with the man of legal age and capable, and the only family model was the one based on heterosexual marriage with offspring biological or by adoption. The proposal involves the analysis of the influences of the “linguistic turn” and the “theory of care” in the conceptualization and normative design of some of the most significant institutions of private law, rescuing the importance of law as a restorative force of subjectivity, highlighting that when the law recognizes individualities, a broader construction of subjectivity is possible.
Keywords: Person; Civil and Commercial Code; Pluralism; Linguist Turn; Care